PARTISIPASI MASYARAKAT DALAM PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN BELLO, KECAMATAN MAULAFA, KOTA KUPANG - M. Suki Dato, Sisilia A.; Kebayantini, Ni Luh Nyoman; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 01 (2021): JISSOROT, 2021)
Kota Tanpa Kumuh (Kotaku) Program aims to reduce the area of ??slum areas and support the realization of livable, productive, and sustainable urban settlements. Based on the results of the research that the author did, the form of community participation in the decision-making process is that the people of RT 018/RW 007 learn politics but there is a little conflict in it. The socio-cultural impact that can be seen is that community mobilization is easier, besides that there is a political impact, namely the people of RT 018/RW 007 learn to make decisions, the perceived environmental impact is that the environment becomes more beautiful and beautiful, and the last is the economic impact, namely the people who help building construction earns additional money from funds and other economic impacts, namely that the community has to pay a fee every month which causes them to have to spend money back.   Keywords: Kotaku, empowerment, community participation, environment, slums.